Comparison of synchronized-ovulation protocols and traditional synchronized-estrus programs using prostaglandin F2(α) - Y. Kobayashi; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1995)
Five treatments were developed to compare a new synchronized ovulation protocol, which programs follicular development with the regression of the corpus luteum, and traditional prostaglandin protocols that only control the regression of the corpus luteum. The synchronized ovulation treatment, which requires no heat detection before a fixed-time insemination, tended to decrease pregnancy rates compared to a similar synchronized ovulation treatment in which inseminations occurred at a detected estrus (30 vs 50%). The traditional two-injection prostaglandin protocol that synchronized estrus by regression of the corpus luteum had a greater pregnancy rate (57%) than similar two-injection prostaglandin protocols in which gonadotropin-releasing hormone (GnRH or Cystorelin®) was used to induce ovulation of the follicle before one fixed-time insemination (21%) or one fixed-time insemination was given in the absence of estrus (18%). The synchronized ovulation protocol improved pregnancy rates compared to prostaglandin protocols with fixed-time inseminations, but in either protocol, in which ovulation or estrus was synchronized, pregnancy rates were always greater when inseminations were performed after detected estrus.; Dairy Day, 1995, Kansas State University, Manhattan, KS, 1995;
Keywords: Dairy Day; 1995; Kansas Agricultural Experiment Station contribution; no. 96-106-S; Report of progress (Kansas Agricultural Experiment Station and Cooperative Extension Service); 742; Prostaglandin; Gonadotropin-releasing hormone; Sychronzied ovulation; synchronized estrus; Pregnancy rates